Death, hope, and sex : steps to an evolutionary ecology of mind and morality - Chisholm, James S. (Cambridge University Press, 1999)
"Following evolutionary theory to its logical conclusion, Death, Hope and Sex uses life history theory and attachment theory to construct a model of human nature in which critical features are understood in terms of the development of alternative reproductive strategies contingent on environmental risk and uncertainity. James Chisholm examines the implications of this model for perspectives on concerns associated with human reproduction including teen pregnancy and young male violence."--Jacket